(untitled) (diségno, 2019)
The main objective of the DATA –Developing Abandoned Transurban Areas– research project, hosted by the University of Padua and financed by the Veneto Region, is to design innovative strategies to recover, regenerate, and enhance abandoned areas located on the margins of the consolidated city. Abandoned urban areas around Padua, the case study of the project, are a particularly important example in consideration of the fact that northern Italy contains the highest increase in land consumption in the country (8.4% in 2013; ISPRA 2015) and, in particular, the city is first in the region for the percentage of land used (49% in 2013; ARPA Veneto 2015). The objective is therefore to build transformation scenarios for development and economic rebirth in reference to sustainable living in compromised urban areas awaiting regeneration. The multidisciplinary structure of the project is organized into six distinct, complementary areas: web GIS; BIM and land information modelling; pilot scenario design; urban planning and feasibility studies; waste recycling; and data management and ICT. (G.P., L.S.).